SKIN SECRETIONS OF BORNEAN FROGS REVEAL ANTIMICROBIAL PEPTIDES WITH INSULIN RELEASING PROPERTIES IN HIT-T15 CELLS - Muna, Sabri; Amera, A. M. Abdalnabi; Zunika, Amit; Ramlah, Zainudin (UMT Press, 2026)
Skin secretion of two Bornean frogs from the Ranidae family, Pulcharana baramica and Hylarana erythraea were evaluated for their antimicrobial and insulinotropic properties. Comprehensive approach and various techniques were employed to study the characteristics of the antimicrobial peptides (AMPs) isolated from these frogs. Crude skin secretions of the frogs were partially purified using Sep Pak C-18 cartridges, followed by further purification via the HPLC AKTA method. The peptides purity was assessed through SDS-PAGE gel which revealed that the HPLC AKTA method produced clearer and cleaner bands, demonstrating its superior efficacy as compared to Sep-Pak. The disk diffusion assay demonstrated significant zones of inhibition against both E. coli and S. aureus, underscoring the peptides' ability to effectively impede bacterial growth. The minimum inhibitory concentration (MIC) assay provided specific MIC values for the tested bacteria. The results showed that the AMPs from Pulchrana baramica were more potent when compared to Hylarana erythraea, with an MIC of 125 µg/ml for E. coli. In terms of cytotoxicity, purified AMPs from both Ranid frogs induced over 50% blood cell lysis, suggesting that they may affect the cell membranes integrity of mammalian erythrocytes. This research further investigates the insulinotropic effect of AMPs from Ranidae frogs on HIT-T15 cells. AMPs from both frog species were able to trigger insulin secretion increase from the pancreatic cells. Statistical analysis indicates a significant difference (p<0.05) for P. baramica, while H. erythraea's effect is not significant (p > 0.05). The current findings suggest that these multifunctional peptides play an important role in the defence of Ranid frogs from invading pathogenic microorganisms present in their environment and may hold potential future applications as an antidiabetic agent in managing glucose levels and diabetes.